DEVELOPMENT OF CATALYST FOR THE PRODUCTION OF BIO-JET FUEL FROM VEGETABLE OILS - Dzaky A, M.
Indonesia has significant potential in utilizing palm oil as bio-jet fuel. With a total area of palm oil plantations reaching 14.59 million hectares and a Crude Palm Oil (CPO) production of 44.76 million tons in 2020. Bio-jet fuel can be produced through the hydrotreating process, including hydrodeoxygenation, hydrocracking, and hydroisomerization with catalysts. The commonly used catalysts include sulfide catalysts, noble metals, and reduced transition metals. However, sulfide catalysts are susceptible to water deactivation, while noble metal catalysts are expensive. Therefore, this research aims to develop reliable and cost-effective reduced transition metal catalysts for bio-jet fuel production. Ni2P and NiMoP catalysts have been synthesized with supports such as Al2O3, ZSM-5, Zeolite-?, and SAPO-11. The feedstock used in the study consists of n-hexadecane and FAME. The research was conducted using a batch reactor (T: 300°C; PH2: 40 bar; RPM: 300). The catalyst with the best HDO (hydrotreating) capability was obtained with Ni2P/Zeolite-? catalyst, achieving a conversion and selectivity of 100% and 69%, respectively. The catalyst demonstrating the best cracking ability was NiMoP/ZSM-5, producing cracking in the bio-jet range of 26%. The catalyst exhibiting the best hydroisomerization ability was Ni2P/SAPO-11, with an isomerization yield of 12% in the bio-jet range.